The Role of Islamic Education in Realizing in Sustainable Development Goals (SDGs 3) - Fadzilah Abd Rahman; Krim Ulwi; Wan Sofea Adlin Binti Wan Aminudin (International Islamic Studies Development and Research Center (IISDRC), 2025)
The concept of health in Islam is an important part of religious teachings. This practice includes guidelines that are not only spiritual in nature, but also need to maintain health socially. In accordance with the sunnah of the Prophet. This article aims to analyze how the practice of maintaining health in Islam should be. This research uses a qualitative method with the type of living Quran and hadith research with data sources taken from the arguments of the Quran and hadith, the results of ijtihad, the opinions of experts. The selection of this living Quran method refers to Engkizar's theory which is based on the needs and objectives of the topic under study. In addition, the author also strengthens data sources from various previous research results that have been published in reputable international journals. All of the above data is analyzed thematically. The findings of this study found four concepts and practices of maintaining health in Islam. The four practices of maintaining health are i) physically healthy, ii) mentally healthy, iii) spiritually healthy, iv) socially healthy. The four concepts of maintaining health in Islam can be used as a reference for all humans in order to maintain good health according to Islamic guidance.